Peran Puskesmas Kuprik Dalam Menurunkan Stunting Di Distrik Semangga - Ardhia Pramestu Ervitaningrum; Syahruddin; Natalia Suryani Purba; Evelin Cornelia Cabuy (Papsel Journal of Humanities and Policy, 2024)
In testing the problem of stunting the government works continously with various health agencies such as the Ministry of Health, the Health Office, the Hospital to the Puskesmas. Puskesmas is the first-level facility and the frontline in serving health problems in the community, the type of research used is a case study by observing the phenomena that occur. The method used is descriptive qualitative and data collection in the form of observation interviews and documentation. The data analysis technique uses three stages: data reduction, data presentation and conclusion drawing. The theory used is Jim Ife’s Role theory with 4 indicators, namely facilitative role, educational role, representative role, and techinal role. In this study, there were 12 informants. The results of study show that the role of Puskesmas Kuprik in declining stunting in the Semangga district has been carried out by running program such as providing additional food, holding classes for pregnant women and toddlers classes, conducting counseling on environmental health, collaborating with other institusions and using applications in recording and reporting nutrition results in the Semangga district area, the role carried out by Puskesmas Kuprik has not been optimized enough because there are still obstacles that occur in several indicators when measured using 4 indicators according to Jim Ife.